Variation in a range of mTOR-related genes associates with intracranial volume and intellectual disability - M. R. F. Reijnders; M. Kousi; G. M. van Woerden; M. Klein; J. Bralten; G. M. S. Mancini; T. van Essen; M. Proietti-Onori; E. E. J. Smeets; M. van Gastel; A. P. A. Stegmann; S. J. C. Stevens; et al. (Nature Communications, 2017)
The mTOR pathway is a key regulator of normal brain development. Here, the authors identify de novo mutations in RHEB, an mTOR activator protein, in patients with intellectual disability associated with megalencephaly and find a role for RHEB in regulating neuronal soma size and migration in vitro and in vivo.